Pregabalin for Opioid-Refractory Pain in a Patient with Ankylosing Spondylitis - Konstantinos A. Kontoangelos; Anastasios V. Kouzoupis; Panagiotis P. Ferentinos; Ioannis D. Xynos; Nikolaos V. Sipsas; George N. Papadimitriou (Case Reports in Psychiatry)
Background. Ankylosing spondylitis (AS) is a systemic inflammatory disease with chronic back pain as the most common presenting symptom. We present a case of a male patient with AS reporting symptoms of severe low back pain, buttock pain, and limited spinal mobility. After chronic treatment with opioids, we administered pregabalin at a dose of 300 mg as an analgesic agent while opioids were discontinued. Findings. Pain symptoms improved progressively, and opioids were gradually discontinued without any withdrawal symptoms reported. Conclusions. Pregabalin is potentially useful in the management of pain in patients with AS while effectively managing the discontinuation of opioid treatment.